SYNONYMOUS PARADIGM OF THE CONCEPT «GOSPODIN» IN THE RUSSIAN LANGUAGE PICTURE OF THE WORLD - E. Vermenskaya; I. Kicheva (Гуманитарные и юридические исследования)
The article considers the verbalization of the concept «gospodin» means synonymous paradigm with the position of the linguocultural approach to the analysis of the concept as units of a nation's culture, the element of the collective heritage of native speakers and a fragment of the world picture. The authors proceed from the position that the content of the concept changes, expands, grows with new shades of meanings and conceptual characteristics, which is especially important for concepts that have been significantly influenced by the cultural and historical factor. The idea is substantiated that the concept «gospodin» in the Russian language picture of the world can be characterized primarily based on the semantics of language manifestations of the concept in the vocabulary of the language. The paradigmatic parameter in the analysis of the concept establishes the role and place of the lexeme - the representative of the concept in the lexical and semantic field that implements the concept in the world picture, taking into account the commonality of integral signs of synonyms. The study is based on the analysis of the data of explanatory, synonymic, etymological dictionaries, the results of the analysis of the functioning of synonyms in works of fiction and journalistic literature. The authors have identiied a model of synonymic paradigm, including synonymic series and their dominants, identiied additional units in the synonymic paradigm of the concept «gospodin», revealing the dynamics of the concept at the present stage.